Phosphorus (P) Adsorption Behavior and Harvested P by the Sugarcane (Saccharum officinarum L.) Affected by Inorganic and Organic Fertilizer Applications on an Ultisol - Lumbanraja, Jamalam; Satgada, Catur Putra; Sarno, Sarno; Utomo, Muhajir; Hasibuan, Rosma; Dermiyati, Dermiyati; Triyono, Sugeng (UNIVERSITY OF LAMPUNG, 2018)
The field and laboratory experimental studies were conducted to determine the phosphorus (P) adsorption behavior employing Langmuir Method and yield of sugarcane as affected by compost and inorganic fertilizer applications, and to determine the correlations between the Langmuir parameters and the availability of P in soil or harvested P by the sugarcane. Both field and lab experiments were arranged in a randomized block design, consisting of five treatments (A= 100% NPK, B=100% compost, C=100% NPK + 50% compost, D= 50% NPK + 100%, compost, and E= no fertilizer).Â Each treatment was replicated three times. Field and laboratory studies were carried out in the sugarcane field and in the Laboratory of Soil Science, the University of Lampung for Langmuir P studies, respectively. The results showed that the applications of 100% NPK plus 50% organic fertilizer, and 100% NPK resulted in the highest amount of available-P in the soil, the lowest maximum adsorption of P (Xm) and the lowest relative bonding energy of P (km); as well as the highest effect on the increase of sugarcane production. On the other hand, the treatments of no fertilizer and the 100% organic fertilizer resulted in the highest maximum adsorption of P (Xm) and the lowest sugar production. There were very significant negative correlations between the maximum adsorption of P (Xm) and soil P, harvested P by the sugarcane and stem biomass; while similar trend but no significant correlations between the relative bonding energy of P (km) and soil P, harvested P, leaf biomass and stem biomass were detected.Â Â